Optimization of Thirst Management on CKD Patients Undergoing Hemodialysis by Sipping Ice Cube - Yunie Armiyati; Khoiriyah Khoiriyah; Ahmad Mustofa (Media Keperawatan Indonesia, 2019)
Excess fluid is a major problem in patients with Chronic Kidney Disease (CKD). CKD patients undergoing hemodialysis must keep limiting fluid intake during the interdialysis period so that excess fluid does not occur. Consequently limiting fluid intake arises thirst and will affect fluid restriction compliance. Management of thirst that can be done in hemodialysis patients, among others, suck ice cubes, gurgling the ripe water and gurgling with mouthwash, each of which has a different action against patients thirst. The purpose of this study was to compare the three interventions "thirst management", namely sipping ice cubes, gargling ripe water and gargling with mouthwash against patient thirst. This study was an experimental study in 27 samples of CKD patients who underwent hemodialysis at Roemani Muhammadiyah Hospital in Semarang divided into 3 groups with each group 9 samples. The results showed that the duration of holding thirst for the group sipping on ice cubes averaged 93 minutes, the gurgling group of ripe water averaged 55 minutes and the average length of time holding the thirst group who gurgling with mouthwash was 69.71 minutes. There was no significant difference in the duration of holding thirst after sucking on ice cubes and gargling ripe water, and gargling with mouthwash (ρ value 0.061). Sipping ice cubes can fight the longest thirst compared to gargling ripe water or gargling with mouthwash. The recommendations of this study are expected to intervene to sipping ice cubes, gargling ripe water and gargling with mouthwash can be used for thirst management in hemodialysis patients.  Hemodialysis patients can choose interventions to reduce the thirst that is most appropriate.